Some Aspects of Developing Cofnitive Skills in Future Doctors - Xamidovich, Supichakov Xondamir (Journal of Innovation in Education and Social Research, 2025)
This article analyzes some didactic and practical aspects of developing thinking skills in future doctors. It considers advanced methods for developing clinical thinking, analytical thinking, and decision-making skills in problem situations in the process of medical education, in particular, approaches based on interactive technologies such as the reflective approach, clinical scenario-based learning, and the SNAPPS model.